Kebijakan Transportasi Online dan Konflik Sosial - Bambang Istianto; Taufan Maulamin (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2017)
This research aims at doing analysis and evaluation forward the governments Policy Concerning “ Online Transportation”. The Policy Nomenclature is in the regulation of transportation ministry No. 26 in 2017 on the implementation of public transportation which is not operating on a certain route online transportation operation has become phenomenal because of causing a social conflict. This has been going on for 2 years and it has not been settled up to now. Public transportation in the field of public administration is called public goods. The Availability and Implementation become the government's obligation. This research aims to do an evaluation on the government policy which has caused a social conflict. The Method of research used is a qualitative-descriptive research. The population in this research is transportation operators such as online taxi drivers, conventional taxi driver, vehicle owners and online taxi users. The sample taking technic done is based on random sampling, to completed the analysis forward the online transportation policy was done an in-depth interview and as “ key informants”, namely” Policymakers” -Online transportation operators. The research of the research thas found that the formulation process of the policy has not been done comprehensively and integrally. There are different perception and definition of the government’s intention and public transportation and definition between the government’s intention and public policy found that the support of an organization, human implementation of the budget suggests that the government improve the formulation and implementation through the strengthening of the support of the reliable and organization and management so that social conflicts won’t take place.